Оn the new procedure for the creation of the arbitration institution (introduction to review) - Y. Gerasimenko; L. Terekhova (Правоприменение, 2017)
УДК 342.951+347.999This informational introductory article is devoted to the peculiarities of the procedure of creation of the arbitration institution according to the new 2015 Federal Law "On arbitration (arbitration proceedings)". The aim of the article is the identification of the new law preconditions to the emergence of administrative barriers in the establishment of arbitral institutions. The study is based on methods of formal law, analysis and synthesis, the sociological method of survey is also used. The results and scope of the results. The article notes the objective difficulties in the establishment of arbitration institutions as well as provides a critical analysis of the innovations in 2015 Federal Law "On arbitration (arbitration proceedings) in the Russian Federation". The procedure for creating the arbitration courts became more bureaucratic and it is focused on filtering such institutions by tightening the requirements. The procedure for creating the arbitration courts can be described as permissive and multi-stage. The second noticeable trend in the 2015 Federal Law is broad sphere of control over arbitration courts and substitution of their competence by a competent court. According to the results of a survey of representatives of the business community authors identify the legislative background of administrative barriers on a way of establishment of arbitration courts. The results of the study can be used in the improvement of legislative procedures for the estab-lishment of arbitration courts. Conclusions. New Law actually creates a "quasi-judicial" bodies, that have highest level of bureaucratization, so arbitration courts lose their main characteristics: contractual and dispositive principles. Novels of Law, aimed at stricter administration and control, are obvious, however, a new quality for arbitration as the most popular form of alternative dispute resolution is still not created.